Outcomes of endoscopic therapy for bleeding peptic ulcers ; a retrospective study in Hospital Serdang - Zaidi, Ahmad Al-Hafeez Ahmad (2020)
Background and objectives: Endoscopic therapy remains the mainstay in treatment of upper gastrointestinal bleeding (UGIB). Despite the advancement in endoscopic therapy, the mortality rate for UGIB has remained constant at about 10% for the past few decades. This study aims to determine the prevalence of outcomes post endoscopic therapy in bleeding peptic ulcers. Methods: This is a retrospective record review of patients who underwent emergency upper endoscopy for UGIB from March 2014 to March 2019 in Hospital Serdang, Selangor. Data was collected from endoscopic suite records and the prevalence of permanent haemostasis, re-endoscopy, angio-embolization, surgery and 30-day mortality was calculated. Results: A total of 204 patients who underwent emergency upper endoscopic therapy for UGIB were included in our study. More than half of the patients 113 (55.4%) achieved permanent haemostasis after initial endoscopic therapy whilst 84 (41.2%) had to undergo re-endoscopy due to re-bleeding ulcer. A small percentage had to undergo surgery 10 (4.9%) while only 3 (1.5%) underwent angio-embolization. Out of 204 patients included, there was 34 (16.7%) mortalities and the median length of stay was 5 days. Conclusion: From our study, we can conclude that permanent haemostasis is the outcome with highest prevalence after endoscopic therapy for UGIB in our centre. However, we should strive to reduce our rate of re-endoscopy as it is not up to par with data from other developing countries.